Studi Kualitatif Perilaku Konsumen pada Fenomena Silent Leads dalam Digital Marketing Amanah Bunda Daycare Semarang - Pangestu Adika Putra; Viro Dharma Saputra (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2025)
This study discusses the phenomenon of silent lead in digital marketing strategy Amanah Bunda Daycare Semarang. This phenomenon refers to potential customers who have made an initial interaction through WhatsApp Business After seeing Meta Ads ads, but then do not continue communication or convert into customers. The phenomenon of silent leads is an important concern because although the digital marketing process manages to reach the target audience and trigger an initial response, the interaction does not continue until the purchase or registration stage of the service. This study uses a descriptive qualitative approach to explore the characteristics of passive behavior. The Data was collected through in-depth interviews with the internal manager of Amanah Bunda Daycare and five informants identified as silent leads. The results showed that the passive attitude of potential customers is influenced by several main factors, namely the location that is considered less strategic or too far, the perception of prices that are considered high, personal conditions such as changes in plans or time constraints, as well as the quality of customer service communication that is perceived to be less than optimal in providing responses, information, and personal approach. This phenomenon has not been fully accommodated in classic conversion models such as Aida (Attention, Interest, Desire, Action) and model 5A (Aware, Appeal, Ask, Act, Advocate). This shows that there are gaps in marketing communication strategies, especially in managing potential customers who initially respond positively but stop before conversion. Therefore, this study recommends the development of a more empathetic, structured and sustainable approach to communication. Suggested strategies include improving customer service systems based on quick response and personalization, implementing polite but consistent follow-up strategies, and composing marketing content that is able to build trust and emotional connection with potential customers. With these measures, it is expected that silent leads can be minimized and conversion rates increased significantly.